The Determination of Total Serum Bilirubin Concentration in Type 2 Diabetes Patients - Mandal, Šaćira (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2021)
Bilirubin represent a natural end-product of heme metabolism and is used as as a marker in diagnosis off hepatobiliary diseases. Recent studies demonstrated that serum bilirubin levels are related to the risk of Type 2 diabetes mellitus (T2D) development and subsequent complications. The aim of this study was to analyzed serum total bilirubin concentrations and its relationship with biochemical and clinical characteristics in T2D patients. Total of 109 participants were included in this study, 54 controls and 55 diabetic patients, both gender, while ages ranged from 35 to 70 years. Biochemical parameters were analyzed by standard IFCC methods while serum total bilirubin concentrations was determined by the method of Jendrassik/Gróf. All analyses and measurements were provided by using the chemical analyzer VITROS 350. Results showed a significant difference in concentrations of glucose, glycated hemoglobin (HbA1c), lipid profile (total cholesterol, triglycerides, HDL cholesterol, LDL cholesterol) and bilirubin between T2D patients and controls (p<0.05). Also, significant association was found between bilirubin and glucose concentrations in two investigated populations (p<0.05). It appears that elevated concentration of bilirubin and biochemical characteristics are associated with the progression development of Type 2 diabetes and its related vascular complications. Therefore, total serum bilirubin concentrations could be used as potential T2D biomarker and therefore, as new therapeutic target.